Current status of nuclear cardiology in the Russian Federation - K. V. ZavadovskyZavadovsky; Zh. V. Vesnina; Zh. Zh. Anashbaev; A. V. Mochula; S. I. Sazonova; Yu. N. Ilyushenkova; V. V. Shipulin; Yu. V. Varlamova; A. A. Ansheles; I. P. Aslanidi; N. M. Valiullina; M. N. Vakhromeeva; et al. (Российский кардиологический журнал, 2023)
The article is devoted to the analysis of the current status of nuclear cardiology in the Russian Federation. The data on the number of facilities performing radionuclide investigations for the diagnosis and monitoring of the treatment of cardiovascular diseases, their staffing and equipment are given. The statistics of the conducted nuclear cardiology tests for 2018-2020 are given, as well as their methods, features and diagnostic significance are described.